A expansão da disponibilidade de crédito PRONAF às comunidades quilombolas do Vale Do Ribeira/SP como expressão da crise imanente do capital - Cecília Cruz Vecina (Geografares, 2019)
The purpose of this paper is to discuss some understandings about the process of capital accumulation (mainly formulated by David Harvey, 2011, and Roswitha Scholz, 2016) through the study of the rise in the quantities of contracts and resources released nationally by the “Programa Nacional de Fortalecimento da Agricultura Familiar” (PRONAF) over the governments of Luiz Inácio Lula da Silva (2003-2010) and Dilma Rousseff (2011-2016) and their distribution history to the quilombola communities in the Vale do Ribeira/SP. This articulation, between the reproduction of capital in its totality, the national economic policy and the particularity of social relations in the quilombola communities, becomes important as a form of analysis that puts these plans in tension, which, we argue, makes it possible to make explicit the limits of accumulation and of the actions taken to circumvent the phenomenal crises of capital. Thus, based on fieldwork conducted between 2015 and 2018 in the cities of Eldorado, Iporanga and Registro (in which we interviewed quilombola farmers, agricultural technicians from the “Fundação Instituto de Terras do Estado de São Paulo” - ITESP -, the “Coordenadoria de Assistência Técnica Integral” - CATI - and financial agents of Banco do Brasil), we sought to present the relationship between access to credit and the promise of “enrichment” that this represents for quilombola families, how the subjects involved understand when defaulting and the relations between these process and the totality given by the reproduction of the capital in general.